Brilliant beetles : a 4D book - Higgins, Melissa, 1953- (Pebble, 2019)
"What makes a beetle a beetle? What are coolest beetles from around the world? Carefully leveled, engaging text supports life science curriculum related to classification, behavior, life cycles, and more"--
Amazing beetles -- Weevils -- Bombardier beetles -- Crawling water beetles -- Skin beetles -- Dung beetles -- Diving beetles -- Fireflies -- Ladybugs -- Longhorn beetles -- Rhinoceros beetles -- Namib desert beetle -- Glossary -- Critical thinking questions.
Includes bibliographical references and index.
Age 4-8.
K to Grade 3.
Keywords: Beetles -- Juvenile literature